Comparison of endoscopic underlay and microscopic underlay tympanoplasty: a prospective research at a tertiary care centre in Gujarat - Sinha, Mohit; Hirani, Narendra; Khilnani, Ajeet Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Tympanoplasty is an ever evolving surgery with myriad of approaches and tools. Use of endoscope is relatively new and there are few studies evaluating the use of endoscope via microscope because of a big learning curve in using one hand endoscopic technique despite it being minimally invasive. Methods: This is a prospective study conducted from June 2016 to May 2017 with a sample size of 44 patients. The study included patients of Chronic Otitis Media (COM) of mucosal inactive type without any co-morbidities in which only Type-1 tympanoplasty was done. The patients were divided into endoscopic or microscopic group using simple random sampling and after taking written and informed consent. The patient’s details regarding audiometric, oto-endoscopic and nasal endoscopic evaluation were recorded. Intra operative findings, duration of surgery and post-operative pain scoring were recorded. The patients were followed up for 3 months and subjected to post-operative audiometry and patient satisfaction questionnaire. The groups were evaluated for graft take up and closure of air bone gap, post-operative complications and patient satisfaction. The results were analysed using descriptive statistics (mean and percentage) and CHISQ test. Results: Graft was taken up in 21 patients (95%) in microscopic as opposed to 20 in endoscopic group (90%). Mean VAS scoring for pain was 2.5 in microscopic group on first post-operative day and 1.5 for the endoscopic group. The mean improvement in air bone gap post-surgery was 23.68 dB (SD=4.94) for microscopic group and 16.13 dB (SD=6.49) for endoscopic group. Conclusions: Endoscopic tympanoplasty as a technique has a long learning curve. The results indicate that endoscopic technique is as efficacious as and less invasive than microscope surgery for doing tympanoplasty.